Borophene: Freestanding Borophene and Its Hybrids (Adv. Mater. 27/2019). Issue 27 (2nd July 2019) - Ranjan, Pranay; Sahu, Tumesh Kumar; Bhushan, Rebti; Yamijala, Sharma SRKC; Late, Dattatray J.; Kumar, Prashant; Vinu, Ajayan
Abstract : Borophene, the lightest elemental Dirac material, is realized experimentally in free‐standing form by solution‐phase synthesis by Prashant Kumar, Ajayan Vinu, and co‐workers, as described in article number1900353 . Various sensing applications are demonstrated, such as in SERS‐based molecular sensing, gas sensing, photo‐sensing, and strain sensing. This new material seems promising for large‐scale applications, such as in hybrid energy storage and in catalysis.